CAM Use and Suggestions for Medical Care of Senior Citizens: A Qualitative Study Using the World Café Method. (18th August 2013) - Stöckigt, B.; Teut, M.; Witt, C. M.
Abstract : Background . Little data exists concerning the reasons for using complementary and alternative (CAM) therapies by seniors. Therefore, the aim of this study is to learn about motives of German seniors for using CAM therapies and their wishes for health care in general. Methods . One focus group and one "World Café" following a semistructured interview guide were conducted. All discussions were recorded digitally, transcribed, and analyzed according to Qualitative Content Analysis using the software MAXQDA. Results . In total 21 seniors participated (eighteen female, three male, mean age 72.5 ± 4.3 years). Most of the participants had lifelong experiences with medicinal herbs and home remedies due to unavailable conventional care during childhood. Also important for them were nutrition and exercise. These methods were often used as self-care to enhance wellbeing, to prevent and to cure illnesses. The participants would welcome an integration of CAM in health care services. They asked especially for more empathic physicians who are better trained in CAM and respect their experiences. Conclusion . The importance of life experience in regard to health care by senior can be seen as a resource. Qualitative studies investigating physician-patient relationships and intergenerational aspects in CAM use could be of interest for further studies.